The Values of Character Building Found in Novel “This Earth Of Mankind” as Educational Media - Afrizal Mukhtarom (Universitas Islam Nahdlatul Ulama Jepara, 2022)
ABSTRACTEvery person needs education to help develop not only physical but mental nature of human beings towards civilisation. This continuous process never stops as it provides fundamental rules for life for adults and young people, and it stresses the importance of helping children learn and practice behaviors that reflect universal ethical values. Each student has distinctive characters and then came the character education/character building in the educational process. The character building intends to develop students’ potential in learning common attitudes, beliefs and behaviors that are important for them to be responsible, kind-hearted citizens. This research tried to dig the values for character building in the novel “This Earth of Mankind” by Pramoedya Ananta Toer as a media on educational process to build students’ characters. The values were taken from the dialog and monolog. Discourse analysis consisting of data display, data reductive, data interpretative was employed to analysis the data of this research. The analysis results indicated values contained in the novel as follows: (1)Love for Reading; (2)Curiosity; (3)Forgiving; (4)Love for Writing; (5)Friendliness; (6)Hard work; (7)Religious; (8)Attitude; (9)Integrity; (10)Honesty; (11)Responsibility; (12)Patriotism; (13)Discipline (14)Independence; (15)Tolerance;Keywords: Discourse analysis, education, character building, educational media.